Membangun Kesadaran dan Ketaatan Hukum Masyarakat Perspektif Law Enforcement - Kamaruddin Kamaruddin (Al-'Adl, 2016)
The role of law in society is to ensure certainty and fairness in public life always there is a difference between the patterns of behavior or conduct governance prevailing in the society with patterns of behavior that is desired by the norms (rules) law. This can cause a problem of social inequality so that at certain times tend to conflict and social tensions which of course can disrupt societal changes as well as the desired direction. Building a litigious society and a law-abiding represents the ideals of the norms that want a just society so that the joints of culture will evolve toward the creation of a system of a society that respects each other, making the public aware of the law and law-abiding is not something easy to turn a hand, because not everyone has the legal awareness. The importance of building community awareness and observance of the law, is expected to support and uphold the institution making the community / rules as to crave fulfillment observance and the rule of law. The role and function of building awareness of the law and observance of the law is to: 1) Stability, 2) Provide social framework to the needs of society, 3) Provide tangible institutional framework of social norms, 4) Interwoven among institutions. Law enforcement is the process of doing an effort for the establishment or the functioning of legal norms significantly as the Code of Conduct in traffic or legal relations in the society and state. Because of the awareness of the values of law and observance of the rule of law in running a whole is a manifestation in mengefektikan rule of law.